Pengaruh Penggunaan Metode REAP (Read, Encode, Annotate, Ponder) Terhadap Kemampuan Membaca Mahasiswa Program Studi Pendidikan Bahasa Jerman Universitas Pattimura - Julius Sabono; Patresia S Apituley; Piet Soumokil (J-EDu Journal - Erfolgreicher Deutschunterricht, 2026)
This study aims to determine the effect of the REAP (Read, Encode, Annotate, Ponder) method on the reading comprehension ability of students in the German Language Education Study Program at Pattimura University. Reading comprehension is one of the essential language skills in foreign language learning, as it plays an important role in understanding, interpreting, and analyzing information presented in texts. Therefore, an effective learning method is needed to enhance students’ active engagement in the reading process. This study employed a quantitative approach using a One Group Pretest–Posttest design. The participants were given a pretest before the treatment and a posttest after the implementation of the REAP method in German reading instruction. The data were analyzed using a t-test to test the research hypothesis. The results of the analysis showed that the calculated t value was higher than the t table value (10.04 > 2.131), indicating a significant difference between the pretest and posttest results. The findings revealed that the REAP method had a positive effect on improving students’ reading comprehension ability. In addition to helping students understand the content of texts more deeply, this method also encouraged them to think critically, identify important information, and reflect on the reading material through the stages of reading, encoding information, annotating, and pondering the text. Thus, the REAP method can be considered an effective and innovative alternative teaching method for improving students’ reading comprehension in German language learning.